Enhancing maize phosphorus uptake with optimal blends of high and low-concentration phosphorus fertilizers - Chen, Chen; Xiang, Yue; Jiao, Xiaoqiang; Gong, Haiqing (Frontiers in Plant Science, 2024)
High-concentration phosphorus (P) fertilizers are crucial for crop growth. However, fertilizers with lower P concentrations, such as calcium magnesium phosphate (CMP) and single super phosphate (SSP), can also serve as efficient P sources, especially when blended with high-concentration P fertilizers like diammonium phosphate (DAP) or monoammonium phosphate (MAP). In this study, we conducted a 48-day pot experiment to explore how blending low-P fertilizers could optimize maize P utilization, using CMP to replace DAP in acidic soil, and SSP to replace MAP in alkaline soil, with five SSP+MAP and CMP+DAP mixtures tested. Key metrics such as shoot and root biomass, shoot P uptake, root length, and soil P bioavailability were measured. We found that maize biomass and P uptake with 100% DAP were comparable to those with 50% CMP and 50% DAP in acidic soil. Similar results were observed for 100% MAP compared to 50% SSP and 50% DAP in alkaline soil. Root biomass and length were largest with 100% MAP in acidic soil and at 100% DAP in alkaline soil, with no significant differences at 50% SSP or CMP substitutions for MAP and DAP, respectively. Furthermore, 50% SSP or CMP substitutions for MAP and DAP increased the content and proportion of the labile inorganic P (Pi) pool (H2O-Pi and NaHCO3-Pi), had a direct and positive effect on Olsen-P. Our findings reveal that 1:1 blends of SSP and MAP in acidic soil, and CMP and DAP in alkaline soil, effectively meet maize’s P requirements without relying solely on high-concentration P fertilizers. This indicates that strategic blending of fertilizers can optimize P use, which is crucial for sustainable agriculture.